2009
DOI: 10.1088/0960-1317/19/6/065027
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-based clamp with a passive hold function for precision position retaining of micro manipulators

Abstract: In this paper the design, modeling and fabrication of a precision MEMS-based clamp with a relatively large clamping force are presented. The purpose of the clamp is to mechanically fix a six-degree-of-freedom (DOF) MEMS-based sample manipulator (Brouwer et al J. Int. Soc. Precis. Eng. Nanotechnol. submitted) once the sample has been positioned in all DOFs. The clamping force is generated by a rotational electrostatic comb-drive actuator and can be latched passively by a parallel plate type electrostatically dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A second reason is, the manipulator can be switched between compliant actuation modes for positioning, and high frequent vibration modes during imaging. A clamping mechanism has been developed for this purpose [34]. In the final design a mechanical clamp with a locking device is integrated.…”
Section: Position Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…A second reason is, the manipulator can be switched between compliant actuation modes for positioning, and high frequent vibration modes during imaging. A clamping mechanism has been developed for this purpose [34]. In the final design a mechanical clamp with a locking device is integrated.…”
Section: Position Controlmentioning
confidence: 99%
“…A mechanical clamping mechanism with a locking device can be integrated in the manipulator for that purpose [34]. Clamping also prevents the six low frequency vibration modes resulting from the compliance in the actuation direction of the folded flexures.…”
Section: Platform Stiffness Blocked and Unblockedmentioning
confidence: 99%
“…A margin should be taken into account for the alignment error between the first and second mask. The fabrication rules for the insulation tranches is further discussed by Brouwer et al [6].…”
Section: B Process Issuesmentioning
confidence: 99%
“…Apart from general accuracy requirements, applications as discussed earlier all have their specific specifications. Here, these are left out of scope, but Brouwer et al, for instance, discuss a passive clamping mechanism for position stability of a combdrive-actuated micromanipulator in a TEM [6].…”
mentioning
confidence: 99%
“…Especially, the external longitudinal static magnetic eld (ELSMF) can induce EMS in arc welding deposition, which can reduce the height of weld bead as well as increase the width of weld bead, namely the increase of the aspect ratio (width-height ratio) of single weld bead. In the AWAM process, it has been demonstrated that parameter control is di cult to achieve the ideally at surface in overlapping deposition process, and the large aspect ratio is bene cial to improve the overlapping accuracy [11] . Furthermore, the transverse crosssection of weld bead assisted by longitudinal static magnetic eld is not symmetrical and tilt to one side due to the tangential-EMS and asymmetrical molten pool [12] .…”
Section: Introductionmentioning
confidence: 99%